THE INFLUENCE OF EDUCATION LEVEL, INCOME AND ENVIRONMENTAL CONDITIONS ON FINANCIAL MANAGEMENT AMONG GUARDIANS OF MI AR RAHIM STUDENTS IN GUNUNGSINDUR SUBDISTRICT - Rahma Sari, Intan; Muliyani; Gunhaerani, Dewi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Efficient financial management is essential for family well-being and growth. In the context of MI Ar-Rahim student guardians in Gunungsindur District, the roles of educational level, income, and environmental conditions in shaping financial decisions are vital. Housewives' adept management of family finances is crucial for creating a prosperous and stable household. This study aims to determine the extent to which the influence of educational level income and environmental conditions on financial management in the Guardians of MI Ar-Rahim students Gunungsindur District. Financial management in the family is a way of managing family finances systematically and carefully through the planning implementation and evaluation stages. Housewives in managing family finances must think smart careful and precise in using finances so that they always create a good family and experience continuous growth. With the ability of housewives to manage family finances in an appropriate manner at the right time in the right place at the right price and with the right quality family welfare will be realized. This research was conducted to find out how the influence of the level of education income and environmental conditions in good financial management.